Metopic suture of Taung (Australopithecus africanus) and its implications for hominin brain evolution - Falk, Dean (National Academy of Sciences, 2012)
The type specimen for Australopithecus africanus (Taung) includes a natural endocast that reproduces most of the external morphology of the right cerebral hemisphere and a fragment of fossilized face that articulates with the endocast. Despite the fact that Taung died between 3 and 4 y of age, the endocast reproduces a small triangular-shaped remnant of the anterior fontanelle, from which a clear metopic suture (MS) courses rostrally along the midline [Hrdlička A (1925) Am J Phys Anthropol 8:379–392]. Here we describe and interpret this feature of Taung in light of comparative fossil and actualistic data on the timing of MS closure. In great apes, the MS normally fuses shortly after birth, such that unfused MS similar to Taung’s are rare. In humans, however, MS fuses well after birth, and partially or unfused MS are frequent. In gracile fossil adult hominins that lived between ∼3.0 and 1.5 million y ago, MS are also relatively frequent, indicating that the modern human-like pattern of late MS fusion may have become adaptive during early hominin evolution. Selective pressures favoring delayed fusion might have resulted from three aspects of perinatal ontogeny: (i) the difficulty of giving birth to large-headed neonates through birth canals that were reconfigured for bipedalism (the “obstetric dilemma”), (ii) high early postnatal brain growth rates, and (iii) reorganization and expansion of the frontal neocortex. Overall, our data indicate that hominin brain evolution occurred within a complex network of fetopelvic constraints, which required modification of frontal neurocranial ossification patterns.